Connections Between a Late Summer Snowstorm Over the Southwestern Tibetan Plateau and a Concurrent Indian Monsoon Low‐Pressure System. Issue 24 (21st December 2018) - Dong, Wenhao; Lin, Yanluan; Wright, Jonathon S.; Xie, Yuanyu; Xu, Fanghua; Yang, Kun; Li, Xin; Tian, Lide; Zhao, Xi; Cao, Dianbin
Abstract: Snowstorms cause more damage to the livelihoods and livestock of more than 2 million herders (~80% of the total population) on the Tibetan Plateau than any other natural disaster. In this study, we investigate an extreme snowstorm over the southwestern Tibetan Plateau (SWTP) that occurred on 18–21 September 2008. We explore sources and transport pathways of moisture to this storm using multiple data sets and a series of regional model simulations. The results show that this snowstorm results from dynamical coupling between an upper‐level trough and a concurrent low‐pressure system over northern India. This tropical‐extratropical interaction provides the dynamical mechanism for the snowstorm to occur: the upper level trough favors southward cold advection upstream of the SWTP while the low‐pressure system over northern India provides an abundant supply of moisture. Model‐based sensitivity tests indicate that large amounts of moisture are transported over the SWTP via both the up‐and‐over and upslope transport pathways. Our findings corroborate that low‐pressure systems over northern India can deliver abundant moisture into the SWTP. The coupling of this abundant supply of moisture with an upper‐level trough further leads to the occurrence of an early snow disaster in this case, aggravating already harsh conditions and causing severe damage. Improved understanding of the interactions between these two types of synoptic systems and the climatic conditions that influence their occurrence would aid the development of effective strategies for climate change adaptation and sustainable husbandry, as well as the mitigation and relief of future snow disasters in this region. Key Points: A snowstorm over the southwestern Tibetan Plateau arises from the interaction of an upper‐level trough and a monsoonal low‐pressure system Moisture for the snowstorm is supplied by the low‐pressure system via both up‐and‐over and upslope transport Daily snowfall and snowfall frequency increase over the southwestern Tibetan Plateau in late summer when LPSs approach northern India